Retinal Imaging Biomarkers and Correlation to Systemic Disease Activity in Pediatric Sickle Cell Disease - Sandra Hoyek, MD; Celine Chaaya, MD; Colin A. Lemire, BS; Omar Halawa, MD; Francisco Altamirano, MD; Natasha M. Archer, MD; Efren Gonzalez, MD; Nimesh A. Patel, MD (Ophthalmology Science)
Purpose: To correlate retinal imaging findings with systemic disease activity in children with sickle cell disease (SCD). Design: A retrospective consecutive series. Subjects: Children with SCD aged ≤18 years who had an ophthalmic examination at Boston Children's Hospital between January 1998 and August 2022 were included. Main Outcome Measures: Systemic findings included the number of hospitalizations, number of strokes, treatment with hydroxyurea, hemoglobin (Hgb), and fetal Hgb levels, and time-averaged mean velocity (TAMV) in the right middle cerebral artery (RMCA) and left middle cerebral artery (LMCA) on transcranial Doppler (TCD). Methods: Total retinal thickness was measured on macular OCT (Spectralis OCT2, Heidelberg Engineering). Vessel density (VD) of the superficial capillary plexus (SCP) and deep capillary plexus (DCP) and superficial foveal avascular zone area were measured on 6 × 6-mm OCT angiography (OCTA) scans. Results: Six hundred six eyes from 303 pediatric SCD patients (53% males) were included. OCT and OCTA images were acquired on 104 (17.2%) and 60 (9.9%) eyes at presentation and on 159 (26.2%) and 100 (16.5%) eyes at the final visit, respectively. When adjusting for race and age, retinal thinning on OCT was associated with a higher frequency of hospitalizations, a higher frequency of strokes, and treatment with hydroxyurea. Retinal thickness in the inferior and temporal macula was positively correlated with TAMV in RMCA and in LMCA. Foveal retinal thickness was positively correlated with Hgb level. Similarly, reduced VD in the SCP and DCP in the inferior temporal macula correlated with a higher number of hospitalizations and strokes. A higher VD of the DCP in the inferior-temporal macula positively correlated with TAMV in RMCA (ρ = 0.328, P = 0.3) and in LMCA (ρ = 0.342, P = 0.029). A higher Hgb level correlated with a higher prevalence (ρ = 0.237, P = 0.037) and severity (ρ = 0.299, P = 0.008) of peripheral retinopathy in HbSC, while it correlated with lower prevalence (ρ = −0.183, P = 0.004) and severity (ρ = −0.185, P = 0.004) of peripheral retinopathy in HbSS genotypes. Visual acuity did not correlate with TCD velocity, Hgb level, or number of hospitalizations in HbSS or HbSC genotypes. Conclusions: OCT and OCTA findings are correlated with the severity of systemic disease in children with SCD. Imaging parameters were better correlated with key outcomes such as stroke and hospitalizations than visual acuity. The results suggest that quantitative measures on retinal imaging could be used as biomarkers to predict systemic disease risk and activity. Financial Disclosure(s): Proprietary or commercial disclosure may be found in the Footnotes and Disclosures at the end of this article.